Sistemas agrários e tipologia: reflexões a partir do uso da análise estatística multivariada - Marques, Laila Garcia (2018)
This thesis presents an analysis of the typology of production systems guided by the Theory of Agrarian Systems and its Agrarian Systems Diagnosis (ASD) methodology. They are both formulated from experiments carried out in the field of the French school of Comparative Agriculture research by Marcel Mazoyer and Marc Dufumier, respectively. This proposition is incorporated as a theoretical framework for the elaboration of typologies using multivariate statistics tools, and more specifically, the Cluster Analysis. The research problem emerges from the context of the Technical, Social and Environmental Advisory Service (ATES) in the State of Rio Grande do Sul and aims to investigate the possibility of performing automatic typologies using these statistical techniques, based on data from the ATES Integrated Rural Management System (SIGRA), an online system which gathers information on all settled families in the state. However, during the research, other issues, which were found through the literature review, were incorporated. Firstly, the gradual emergence of the systemic approach was found to be the guiding approach of the Theory of Agrarian Systems in the scientific context from the twentieth century on, which promoted the shaping of a distinct intellectual environment. Thus, the development of systemic theories has influenced agriculture-related research in a context of considerable criticism after the 1960s, which included the findings of the limitations in the research, technology and development model. In the French context, such criticisms are related to the need for developing technologies which are coherent to the farmers’ actual contexts and are also related to the failure of countless development projects and programs. These distinctive elements constituted an environment in which concepts such as agrarian and research-development systems emerge, the latter being related to a way of intervention. The development and institutionalization of the concept of agrarian systems in that context set up a scientific field of research with different perspectives, including the Theory of Agrarian Systems. Overall, the criticism converged on the need for establishing some prior knowledge of the farmers’ actual contexts, which led to the incorporation of typology as a methodological tool to guide and structure the research on theoretical guidelines in the stages of diagnosis and technical support to farmers. In accordance with the steps and principles of the ASD, we sought to map and analyze how these typologies have been elaborated in Brazilian theses and dissertations, based on a state of knowledge. In particular, we sought to identify how multivariate statistics tools are incorporated in this process. Finally, to achieve the proposed goal, a typology of production systems was carried out through Cluster Analysis. The use of this tool allowed for important methodological reflections. Thus, whereas the incorporation of this technique allows the use of a great number of variables and data, it has limitations regarding the apprehension of the dynamics of production systems, and its interpretation analysis is more time-consuming when compared to the ASD. Therefore, it is worth noting that the comprehensiveness of ASD can result in coherent and adequate typologies, especially in relation to the complex and systemic nature of the object under study.